2002
DOI: 10.1113/jphysiol.2001.013293
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage‐arrested cell triplets from ascidian embryo differentiate into three cell types depending on cell combination and contact timing

Abstract: During early ascidian development, which is a prototype of early vertebrate development, anterior neuroectoderm cells (a4.2) from the eight-cell embryo are destined to become anterior neural structures including the brain vesicle, while presumptive notochordal neural cells (A4.1) become larval posterior neural structures including motoneurons. Whereas, an anterior quadrant cell (A3) of the four-cell embryo, from which both anterior neuroectoderm (a4.2) and notochordal neural cells (A4.1) are derived, has both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 41 publications
(124 reference statements)
2
16
0
Order By: Relevance
“…Since the 2C cell is naturally fated to become a half body, and thus its totipotency is similar to that of a fertilized egg, we expected the 2C cell to respond to various inductive stimuli and become any type of differentiated cells in a controllable way. The inductive stimulus tested was the cell contact with one of four cell types from a cleavage-arrested Halocynthia eight-cell embryo, in which we have demonstrated that major differentiation commitment to either epidermal or neural or notochordal or muscular type is initiated (32,33,51). This situation is similar to that of mammalian embryonic stem cells, differentiation of which is most successfully controlled when they were transplanted into early embryonic tissues (56).…”
mentioning
confidence: 76%
See 4 more Smart Citations
“…Since the 2C cell is naturally fated to become a half body, and thus its totipotency is similar to that of a fertilized egg, we expected the 2C cell to respond to various inductive stimuli and become any type of differentiated cells in a controllable way. The inductive stimulus tested was the cell contact with one of four cell types from a cleavage-arrested Halocynthia eight-cell embryo, in which we have demonstrated that major differentiation commitment to either epidermal or neural or notochordal or muscular type is initiated (32,33,51). This situation is similar to that of mammalian embryonic stem cells, differentiation of which is most successfully controlled when they were transplanted into early embryonic tissues (56).…”
mentioning
confidence: 76%
“…These currents are to charge the neighboring cell membrane capacity from the voltage-clamped cell through gap junctional communication (GJC). The ramp potential change had a gradient of 2.0 mV/ms and was applied from a holding potential of Ϫ75 mV for 10 ms, keeping the test potential changes within Ϯ 20 mV until the end of the slope, as described previously (51). Care was taken not to evoke potential-dependent conductances.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations